Identifikasi Status Hara Nitrogen Fosfor dan Kalium Pada Lahan yang Ditanami Tomat di Kecamatan Langowan Barat Kabupaten Minahasa - Kumolontang, Wiesje Junnieke Nathsuo; Kamagi, Yani Ezrah Bartolomeus; Sinolungan, Meldi Tineke Magdalena; Kawulusan, Rafli Irland (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2026)
The purpose of this study was to determine the availability status of N, P, and K nutrients in tomato-planted land, which serves as the basis for fertilizer recommendations for tomato crops. The research was carried out over 8 months. The tools used included shovels and laboratory equipment for soil analysis. The materials used were dryland soil and chemical reagents according to the methods of soil analysis for N, P, and K. The research method employed a survey approach with composite soil sampling at 6 locations, adjusted to the actual soil conditions in the field. Condition 1: Soil that had been prepared and was ready for planting. Condition 2: Soil planted with tomatoes aged 1 month. Condition 3: Soil that had just been harvested, with tomato plants aged 3 months. From each soil condition, 3 soil samples were taken, resulting in a total of 9 samples. The research duration was 8 months, from preparation to the final report. Soil samples collected in the field were analyzed in the laboratory to obtain quantitative results. Nitrogen content was analyzed using the Kjeldahl method; available Phosphorus content was analyzed using the Bray I method; available Potassium content was analyzed using the Bray I method. The data obtained from soil analysis showed that Nitrogen levels were classified as moderate, available Phosphorus levels were moderate, and Potassium was sufficiently available for plant needs.